2016
DOI: 10.4314/ejhs.v26i5.2
|View full text |Cite
|
Sign up to set email alerts
|

Insulin sensitivity and plasma glucose response to aerobic exercise in pregnant women at risk for gestational diabetes mellitus

Abstract: BACKGROUND: Gestational diabetes mellitus (GDM) is one of the common complications that occur during pregnancy. Early intervention is essential to prevent the development of the disease in the nonpregnant state but also helpful in preventing the occurrence of GDM. The aim of the study was to assess the effect of aerobic exercises on insulin sensitivity and fasting plasma glucose level in pregnant women with risk for gestational diabetes mellitus. MATERIALS AND METHODS: Forty multigravidae women between 20-24 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 23 publications
2
17
0
1
Order By: Relevance
“…This is supported by the literature showing that moderate maternal physical activity during gestation is associated with an increase in placental size and function and higher blood volume (Clapp, 2006), which may explain the increase in lean mass (Bisson et al, 2017). Moreover, endurance training during pregnancy is known to improve insulin sensitivity and to reduce circulating insulin levels in mothers (Embaby et al, 2016). Although we did not measure circulating growth factor or insulin levels in our study, others have reported increased body mass and plasma IGF1 concentrations in fetuses from mothers that exercised prior to and during pregnancy compared with those from sedentary mothers (Mangwiro et al, 2018).…”
Section: Discussionsupporting
confidence: 52%
“…This is supported by the literature showing that moderate maternal physical activity during gestation is associated with an increase in placental size and function and higher blood volume (Clapp, 2006), which may explain the increase in lean mass (Bisson et al, 2017). Moreover, endurance training during pregnancy is known to improve insulin sensitivity and to reduce circulating insulin levels in mothers (Embaby et al, 2016). Although we did not measure circulating growth factor or insulin levels in our study, others have reported increased body mass and plasma IGF1 concentrations in fetuses from mothers that exercised prior to and during pregnancy compared with those from sedentary mothers (Mangwiro et al, 2018).…”
Section: Discussionsupporting
confidence: 52%
“…Ebert et al [ 29 ] observed that homeostasis model assessment of insulin resistance (HOMA-IR) remains as a positive predictor of irisin serum concentrations. It should be underlined that physical activity of moderate to high intensity significantly decreases insulin resistance in pregnant women [ 30 ]. We can assume that physical activity removes the potential cause for higher secretion of irisin.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding aerobic exercise, the study found that aerobic exercise improves glycemic control, [93][94][95][96][97][98][99][100][101][102][103][104] insulin sensitivity, [105][106][107] insulin action, 70 body composition, 99 quality-of-life, 108 physical capacity, 99 nerve function, 109 functional capacity, 110 and cardiorespiratory fitness, 101,111 reduces insulin resistance, 97,112,113 insulin levels, 96 lipid profile, 97 BP, 97,100 cardiovascular risk, 106 hemoglobin A1c (HbA1c) levels, 95,111 and waist circumstances, 100 and modulates inflammatory cytokine levels 113 and adipocytokines 113 in T2DM patients.…”
Section: Management Of T2dmmentioning
confidence: 99%